ECONOMIC MODELING OF SUSTAINABLE RURAL DEVELOPMENT UNDER THE CONDITIONS OF DECENTRALIZATION: A CASE STUDY OF UKRAINE - Nataliia KHOMIUK; Olena BOCHKO; Nataliia PAVLIKHA; Anton DEMCHUK; Olena STASHCHUK; Tetiana SHMATKOVSKA; Nataliya NAUMENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The content of rural territories development as a socio-economic-ecological system has been determined. It has been also proved that the study of rural development is of crucial importance because of the necessity to solve some socio-economic problems such as preservation of local customs, historical and ethnic characteristics. We have identified the decentralization as one of the vital components of democratic reformation, contributing to the transparency of the authorities’ activity. The impact of decentralization processes on the indicators of sustainable rural development in Ukraine has been revealed. It manifests itself in the growth of employment and income of rural population, provision of medical and educational institutions, enhancements of road transport infrastructure, creation of conditions for business development and further diversification of economic activity in rural areas, environmental protection. The analysis of sustainable development of rural territories in the conditions of decentralization based on the application of the proposed methodology has been done. Integral indices of sustainable development of rural territories of Ukraine have been calculated using the determination of partial indices of social sphere development, economic and ecological situation. The results of modelling rural territories sustainable development in the context of decentralization can be used to make management decisions for the development and implementation of economic instruments with the aim of achieving such strategic prospects as reformation of local self-governments and territorial organization of central government in Ukraine. To analyze the impact of decentralization on achieving sustainable rural development prospects, the benefits and risks of this process have been identified.